Ecological Importance of Landscape Plants - Sullieva Suluv Khurramovna; Xandalova Sharofat (American Journal of Biology and Natural Sciences, 2024)
Landscape plants are essential to ecological stability, contributing significantly to ecosystem services such as carbon sequestration, air purification, soil stabilization, water management, and biodiversity support. This study examines the ecological functions of landscape plants in various environments, highlighting their role in mitigating climate change, enhancing air and soil quality, preventing erosion, promoting water retention, and providing habitats for diverse species. Findings underscore the importance of integrating a diverse array of plants into urban and rural landscapes to foster environmental resilience and sustainability. The ecological benefits of landscape plants demonstrate their value not only in beautifying spaces but also in supporting crucial environmental processes, making them indispensable to sustainable development and ecological health.